Complete chloroplast genome of Petrocosmea qinlingensis (Gesneriaceae), a protected wild plant in the Qinling mountains - Chao-Qun Li; Qian Mu; Yun Li; Sheng-Long Kan; Guang-Xiao Liu (Mitochondrial DNA. Part B. Resources, 2024)
AbstractPetrocosmea qinlingensis is a protected wild plant endemic in China, inhabiting low-light limestone cliffs but the complete chloroplast genome has not been reported. In this study, we first sequenced and assembled the complete chloroplast genome of P. qinlingensis. The total size of this genome was 153,865 bp, including a large single-copy (LSC) region (84,737 bp), a small single-copy (SSC) region (18,244 bp), and two inverted repeats (IRs) regions (25,442 bp). This genome encoded 111 uniquegenes, consisted of 77 protein-coding genes, four ribosomal RNA genes, and 30 transfer RNA genes. Phylogenomic analysis based on the chloroplast protein-coding genes and showed that the genus Petrocosmea was the closest relative to Raphiocarpus. Our results will support further phylogeographic, population genetic studies of this species.